Physicochemical Characterization of Chitosan-Based Coating-Forming Emulsions: Effect of Homogenization Method and Carvacrol Content - Osorio-Lira, F (Elsevier, 2016)
The effect of carvacrol content and two homogenization methods on the physicochemical properties of chitosan-based coating-forming emulsions were evaluated. Coating-forming emulsions were developed based on chitosan (1.5% w/v) and carvacrol (0.25%, 0.5% and 1.0% v/v) and using two homogenization methods (rotor-stator and rotor-stator followed by high-pressure homogenization). Emulsions were characterized in terms of droplet size, polydispersity index, ζ-potential, rheological behavior, and surface tension. Wettability was evaluated on the cherry tomato epicarp by measuring the critical surface tension and contact angle. Emulsions with smaller droplet size, lower polydispersity index, and higher ζ-potential were obtained by high-pressure homogenization (HPH). Emulsions viscosity decreased when high pressure was applied. Emulsion wettability improved with carvacrol content and HPH. Incorporating carvacrol and using HPH produced emulsions with better functional properties, which could be used as a coating for fruit and vegetable products. © 2016 Elsevier Ltd